Retinal Nerve Fibre Layer Thickness Change Following Femtosecond Laser-Assisted in situ Keratomileusis - Yang Jiang (Frontiers Media S.A., 2021)
Purpose: To evaluate the effect of femtosecond laser-assisted in situ keratomileusis (FS-LASIK) on retinal fovea thickness, volume, and retinal nerve fibre layer (RNFL) thickness.Methods: Thirty-seven eyes (37 patients) undergoing FS-LASIK were included in this prospective study. Optical coherence tomography (OCT) was performed 1 day before, 1 h and 1 day after FS-LASIK surgery.Result: Eighteen male and nineteen females were enrolled. Mean patient age was 22.94 ± 4.22 years. One hour postoperatively, macula fovea thicknesses, macula fovea volume, macula parafovea thickness, macula parafovea volume, macula perifovea thickness, macula perifove volume, temporal RNFL thickness, and superior RNFL thickness measures showed significant decrease (t = 6.171, 6.032, and 9.837, 9.700, 2.532, 4.393, 4.926, 2.265; p = 0.000, 0.000, 0.000, 0.000, 0.016, 0.000, 0.000, and 0.011). Day 1 post-operation, macula fovea thicknesses, macula fovea volume, macula parafovea thickness, macula parafovea volume, and inferior RNFL thickness measures showed significant change compared to preoperative measures (t = 3.620, 3.220, 2.901, 2.910, 3.632; p = 0.001, 0.003, 0.006, 0.006, and 0.001).Conclusion: Our data suggest there are alterations in retinal foveal and RNFL measurements by OCT 1 h and 1 day after FS-LASIK surgery.